CHEMICAL AND BIOCHEMICAL PROFILE OF FILAMENTOUS NON-TUBERCULOUS MYCOBACTERIA ISOLATED FROM CASEOUS LESIONS IN SUDAN (Journal of Veterinary Medicine and Animal Production, 2022)
The aims of this study are to isolate the possible mycobacterial causes ofcaseated bovine tissues and subsequently identify the filamentous farcy agents using chemotaxonomic profile. A total of 59 acid fast filaments were isolated from bovine caseous lesions in South Darfur State. The isolates were conventionally identified using cultural and microscopic tests. For biochemical analysis 32 isolates were investigated while, the chemical profile applied for 24 isolates. Toluene-Acetonitrile precipitation method was applied to determine the quantitative mycolic acid precipitation. Subsequently thin layer chromatography was done from the precipitates for qualitative mycolates. Chloroform / methanol method was applied for typing phenolic glycolipids.Rapidly growing filamentous mycobacterial isolates (n = 32) were identified as M. farcinogenes (n =26) and M. senegalense (n =6) by their biochemical profiles, glycolipids and mycolic acid patterns. Mycolic acid analysis hasa reliable role in differentiation and taxonomy of Mycobacteria from Nocardia and other related bacteria. However glycolipids test could differentiate the farcy agents into M. farcinogenes and M. sengelenses.